Perbedaan Efektivitas Daun Salam dengan Mentimun pada Lansia Hipertensi - Hasliani Hasliani; Nerry Endah N (Sarana Ilmu Indonesia (salnesia), 2021)
During the last 10 years, it is estimated that there has been a significant increase in hypertension patients, which has contributed to the death of approximately 8 million people annually worldwide. The purpose of this study was to analyze the differences in the effectiveness of Indonesian bay leaves solution and cucumbers in elderly with hypertension at Puskesmas Moncobalang, Gowa Regency in 2019. The research method was quantitative with Quasi Experimental design and Non-Equivalent Control Group Design. The results of the Wilcoxon statistical test on Indonesian bay leaves solution with a value of Pvalue 0,005 <0,05, this means that Ho has been rejected and Ha has been accepted. The average pretest score of 3,80 is smaller than the average posttest score of 1,80. Thus, there is the effectiveness of boiled Indonesian bay leaves solution in elderly with hypertension. Likewise, the Wilcoxon statistical test results on cucumbers showed a value of Pvalue 0,004 <0,05, this means that Ho has been rejected and Ha has been accepted. The means of blood pressure pretest is 3,80 which is smaller than the posttest average value of 2,50. This research inferred that the juiced cucumber is effective in treating elderly with hypertension. In conclusion, there is no difference in effectiveness between boiled Indonesian bay leaves solution and juiced cucumber in treating elderly with hypertension at Moncobalang Health Center, Gowa Regency.